Acute Acoustic Trauma in the French Armed Forces During 2007–2014 - Medina-Garin, Doris R. (Noise Health, 2016)
CONTEXT: Despite existing preventive measures, the number of acute acoustic trauma (AAT) cases reported to the French Military Epidemiological Surveillance System (MESS) remains high. AIMS: The objective of this study was to describe AAT and the preventive measures already implemented. SUBJECTS AND METHODS: We conducted a descriptive cross-sectional analysis of AAT using data from the MESS for the period 2007–2014. In addition, we reviewed the current prevention measures that exist in the French armed forces. STATISTICAL ANALYSIS USED: Comparisons between different incidence rates were made by Poisson and quasi-Poisson regression. RESULTS: Between 2007 and 2014, 10,487 AAT cases were reported to the MESS, with a significant decrease in 2013 (P < 0.001). AAT incidence rates were the highest among those aged <25 years − 14.3 per 1000 person-years (PYs) (P < 0.001), and those in the army; with 8.1 per 1000 PYs (P < 0.001), and men had almost twice the risk of women (P < 0.001). AAT mainly occurred in training schools or at camps during exercises. The main prevention actions identified were the following: official regulations, education, making hearing protection devices (HPDs) available for all service members, and regular hearing monitoring. A working group has been set up and has proposed an informative chapter in the weapon handling instruction book, an AAT simulator, and a new HPD, the 3M(®) earplug, with an information brochure. CONCLUSIONS: AAT rates decreased from 2007 to 2014 in the French armed forces. Further analysis is needed to identify the underlying factors involved to improve the prevention actions proposed. The MESS and targeted surveys will assess the impact of the different prevention measures implemented.